(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical characteristics of suicidal ideation and analyze associated factors in post-stroke inpatients at the National Geriatric Hospital. Methods: A cross-sectional descriptive study was conducted on 304 post-stroke patients treated at the National Geriatric Hospital from August 2025 to February 2026. Results: The prevalence of suicidal ideation was 11.8%. Suicidal ideation was more frequently observed among male patients, younger patients, and those with complete dependence due to post-stroke sequelae (p < 0.05). Most cases of suicidal ideation occurred within the first year after stroke diagnosis. Suicidal thoughts commonly occurred several times per week (66.7%) and at multiple times of the day. The most frequently reported contexts were feeling like a burden to others (97.2%) and experiencing restlessness or anxiety with a wish to end suffering (83.3%). Conclusion: Suicidal ideation was identified in 11.8% of post-stroke inpatients and was associated with several sociodemographic and stroke-related clinical factors. Early screening for suicidal ideation and related risk factors is essential for timely intervention and suicide prevention in post-stroke care.